1999
DOI: 10.1177/027112149901900403
|View full text |Cite
|
Sign up to set email alerts
|

Early Intervention Program Practices That Support Collaboration

Abstract: Partnerships between parents of infants and toddlers with special needs and their service coordinators are developed within the context of early intervention program practices that can either support or hinder effective collaboration. The purpose of this study was to explore parents' and service coordinators' perceptions of program practices that affected collaboration. A qualitative analysis of responses to open-ended survey questions from 397 parents and 226 service coordinators yielded five categories and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 10 publications
3
73
0
1
Order By: Relevance
“…Similarly, an exploration of retention and turnover among child welfare and human service workers found that high turnover impeded effective delivery of services, disrupted continuity of care, and contributed to the deterioration of rapport with those served (Barak et al 2001). Moreover, in a study of team factors that contribute to collaboration in parent and service provider teams working to treat children with special needs, collaboration was enhanced when service coordinators had regular and consistent contact with families (Dinnebeil et al 1999). Notably, caregivers specifically identified turnover among service providers as a key factor that detracted from collaboration and care (Dinnebeil et al 1999).…”
Section: Team Attendance Consistencymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, an exploration of retention and turnover among child welfare and human service workers found that high turnover impeded effective delivery of services, disrupted continuity of care, and contributed to the deterioration of rapport with those served (Barak et al 2001). Moreover, in a study of team factors that contribute to collaboration in parent and service provider teams working to treat children with special needs, collaboration was enhanced when service coordinators had regular and consistent contact with families (Dinnebeil et al 1999). Notably, caregivers specifically identified turnover among service providers as a key factor that detracted from collaboration and care (Dinnebeil et al 1999).…”
Section: Team Attendance Consistencymentioning
confidence: 99%
“…Moreover, in a study of team factors that contribute to collaboration in parent and service provider teams working to treat children with special needs, collaboration was enhanced when service coordinators had regular and consistent contact with families (Dinnebeil et al 1999). Notably, caregivers specifically identified turnover among service providers as a key factor that detracted from collaboration and care (Dinnebeil et al 1999).…”
Section: Team Attendance Consistencymentioning
confidence: 99%
“…TRUST Parent Comments. Trust is a term often used in the literature related to developing positive relationships between providers and families (e.g., Dinnebeil et al, 2000). Parent participants used the term "trust" in the context of three distinct meanings.…”
Section: Skillsmentioning
confidence: 99%
“…Flexibility was the primary program characteristic identified by both parents and service coordinators as promoting collaboration with families in an investigation of early intervention program practices by Dinnebeil, Hale, and Rule (1999). Families valued flexible options in scheduling and in how services were delivered.…”
mentioning
confidence: 99%